Predictors of the severity of oral submucous fibrosis among gutka consumers: a regression analysis. Issue 6 (July 2021) - Siddiqui, H.K.; Khan, F.R.; Sadiq, A.; Hashmi, U.; Qaiser, Z.
Abstract: Oral submucous fibrosis (OSMF) is an insidious chronic disease of the oral mucosa that is characterised by severely limited mouth opening, blanching of the oral mucosa, and a burning sensation in the oral cavity. Consumption of betel nut and/or gutka are the known risk factors. We undertook this study to correlate the frequency and duration of gutka intake with the severity of OSMF and to determine the predictors of severe OSMF (mouth opening <20mm). A cross sectional study was conducted on 300 participants (who were known gutka chewers) selected at the Baqai Dental College and Fatima Hospital, Karachi, Pakistan. Participants' medical and dental histories were recorded. Informed consent was obtained, and clinical oral examination was done. Information regarding the extent of mouth opening, chewing habits, frequency and duration of gutka intake, the site of placing gutka, duration of chewing, and whether they swallowed or spat out the gutka were collected. A standardised questionnaire was used to document the findings. Binary logistic regression was applied using the severity of OSMF (mouth opening <20mm) as an outcome variable. Out of 300 participants, 172 (57.3%) were males; mean (SD) age of the sample was 38.2 (12.3) years. A total of 156 (52%) participants had the habit of chewing gutka, of which 213 (71%) had clinical stage I OSMF, 75 (25%) had stage II, and 12 (4%) had stage III. As per functional staging, 18 (6%) subjects had mouth opening <20mm. Nearly 144 (48%) participants were consuming other forms of tobacco in addition to the gutka. Patients with palpable bands = 232 (77.3%), ulcerative lesions = 212 (70.7%), altered taste sensation = 210 (70%) and altered hunger = 252 (85.7%) were common findings. The duration of gutka intake was found to be positively correlated with the severity of OSMF; however; its frequency was not. Among intraoral findings, the presence of red and white lesions inside the mouth was the most significant predictor of the severity of OSMF.